2000
DOI: 10.1897/1551-5028(2000)019<1893:gdaeri>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

GONADAL DEVELOPMENT AND ENDOCRINE RESPONSES IN JAPANESE MEDAKA (ORYZIAS LATIPES) EXPOSED TO o,p′-DDT IN WATER OR THROUGH MATERNAL TRANSFER

Abstract: Abstract-Various isomers and metabolites of DDT disrupt endocrine systems and gonadal development in fish and wildlife, and o,pЈ-DDT has been shown to be an relatively potent estrogen agonist. In this study, we exposed Japanese medaka (Oryzias latipes) to o,pЈ-DDT using two exposure protocols: direct exposure of early life stages to aqueous solutions from 1 to 100 d posthatch and exposure of female medaka to aqueous solutions, followed by mating with unexposed males to produce offspring that were exposed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 34 publications
2
67
1
Order By: Relevance
“…Female white croakers (Genyonemus lineatus) collected from San Pedro Bay, California, with body burdens of ≥ 3.8 ppm ΣDDT (total of all isomers of DDT and its breakdown products) could not be induced to spawn and exhibited only earlystage oocytes, of which high numbers were atretic relative to reference fish (Hose et al 1989). In contrast to our results, Metcalfe et al (2000) reported advanced oogenesis in female medaka developed from eggs with o,p´-DDT concentrations of approximately 80-102 ng/egg, although both reference and treated groups began producing viable eggs at the same time. Males in this same study did not display small gonads and associated secondary sexual effects (lack of breeding tubercles) that we observed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Female white croakers (Genyonemus lineatus) collected from San Pedro Bay, California, with body burdens of ≥ 3.8 ppm ΣDDT (total of all isomers of DDT and its breakdown products) could not be induced to spawn and exhibited only earlystage oocytes, of which high numbers were atretic relative to reference fish (Hose et al 1989). In contrast to our results, Metcalfe et al (2000) reported advanced oogenesis in female medaka developed from eggs with o,p´-DDT concentrations of approximately 80-102 ng/egg, although both reference and treated groups began producing viable eggs at the same time. Males in this same study did not display small gonads and associated secondary sexual effects (lack of breeding tubercles) that we observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Males in this same study did not display small gonads and associated secondary sexual effects (lack of breeding tubercles) that we observed. However, when Metcalfe et al (2000) exposed these male progeny to estradiol at 10 months of age, they found that the male offspring showed significantly greater induction of vitellogenin than did controls, suggesting that early DDT exposure may have potentiated vitellogenin induction later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These nominal concentrations were selected in the context of field measurements from a survey done in an urban reserve in South Africa (Bornman et al, 2007). The concentrations also fall within the sub-lethal range that has been tested by other authors (Benton et al, 1994;Metcalfe et al, 2000;Cheek et al, 2001). The fish were kept under a 12:12 light:dark (LD) cycle regulated by electric timers throughout the exposure period, and the water temperature at 25-28 °C.…”
Section: Test Organismsupporting
confidence: 73%
“…Technical-grade DDT contains 65-80% p,p'-DDT, 15-21% o,p'-DDT and up to 4% p,p'-DDD (bis[4-chlorophenyl]-1,1,-dichloroethane) (ATSDR, 2002). The o,p-isomer constitutes about 15% of technical-grade DDT, and has been reported to be weakly estrogenic (Donohoe and Curtis, 1996;Metcalfe et al, 2000;Papoulias et al, 2003). DDTisomers, including o,p'-DDT have been implicated in reduced development of penises in male alligators from a contaminated Lake Apopka, Florida, USA (Guillete et al, 1994).…”
Section: Introductionmentioning
confidence: 99%